2007
DOI: 10.1002/mds.21369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on geriatric depression scale performance in Parkinson's disease

Abstract: The purpose of this study was to compare the validity of the 15-item Geriatric Depression Scale (GDS-15) in nonelderly (<65 years), young-elderly (age, 65-75), and old-elderly (>75 years) patients with Parkinson's disease (PD). 57 nonelderly, 88 young-elderly, and 81 old-elderly PD patients were administered the GDS-15 and the Structured Clinical Interview for DSM-IV depression module. Receiver-operating characteristic (ROC) curves were plotted for GDS-15 scores against a DSM-IV diagnosis of major or minor dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…23 It has been validated in non-geriatric adults. [24][25][26] The scale range is from 0 to 15, with a higher score indicating a greater number of depressive symptoms. A score of 5 or higher is 60% sensitive and 89% specific for a diagnosis of depressive disorder.…”
Section: Measurementsmentioning
confidence: 99%
“…23 It has been validated in non-geriatric adults. [24][25][26] The scale range is from 0 to 15, with a higher score indicating a greater number of depressive symptoms. A score of 5 or higher is 60% sensitive and 89% specific for a diagnosis of depressive disorder.…”
Section: Measurementsmentioning
confidence: 99%
“…the self report 15 item Geriatric depression Scale was chosen as a succinct mood scale. Although this was initially developed for use with older people, it has since been validated in younger adults (16)(17)(18). the result was dichotomised for analysis to those unlikely to have depression (score 0-4) and those likely to have depression (score 5-15), as previous research has shown 4/5 to be the optimal cutting score (19).…”
Section: Predictor Variablesmentioning
confidence: 99%
“…However, this was examined in 2007, and the GDS-15 demonstrated validity in nonelderly and elderly patients with PD. 48 There was a lack of reporting consistency or absence of important underlying population characteristics; for example, factors such as disease severity, patient assessment in "on" or "off" state, treatment for depression, or history of depression in the dataset. 11,49 This meant that further subgroup analysis of the estimates based on these factors was not possible.…”
mentioning
confidence: 99%